Tradisi Puasa Mutih menjelang pernikahan: Spritual Education bagi calon pengantin wanita - Mutimmatul Faidah; Nur Puji Yanti; Eliya Najma Muntazeri (Jurnal Penelitian, 2022)
Mutih fasting is a tradition for the bride before the wedding ceremony in Purwokerto, Pati village, Central Java. This study aimed to describe the implementation and meaning of mutih fasting undertaken by prospective brides and determine the value of mutih fasting spiritual education for the brides. This qualitative descriptive study was conducted from August to December 2021. Data were collected by using observation and interviews. The obtained data were analyzed using the phenomenology approach. The results showed that mutih fasting allowed them to get closer to Allah. For prospective brides, fasting was interpreted as an inner preparation by cleansing the heart and soul to achieve wedding success and blessings. Physically, it was interpreted as an effort to suppress appetite so that the bride looked more beautiful, and their aura radiated. Another finding showed that spiritual education was a process of self-purification (Takhalli) for the bride, adorning themselves with noble character (Tahalli), and feeling togetherness with Allah (Tajalli). After this tirakat, it was hoped that the bride had physical and spiritual readiness to enter domestic life, became a pious wife with a clean soul, behaved well and wisely, and received God's protection and help.